Quality Performance of Manufacturing Companies in West Java: SCM, TQM, and JIT Impact - Nurul Aziz Pratiwi; Ervan Susilowati; Syukriah Syukriah; Didi Pianda; Erna Susanti (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to analyze the impact of supply chain management (SCM), total quality management (TQM), and just-in-time (JIT) practices on the quality performance of manufacturing companies in Jawa Barat, Indonesia. The manufacturing sector in Jawa Barat plays a crucial role in the regional economy, making it imperative for companies to maintain high-quality standards to remain competitive. Data were collected through surveys and interviews from a sample of 40 manufacturing companies in Jawa Barat. The analysis included statistical techniques such as t-tests and F-tests to examine the relationships between SCM, TQM, JIT, and quality performance. The results indicated that SCM, TQM, and JIT practices have a significant positive influence on quality performance. The calculated t-values and F-value were found to be greater than the critical values, indicating statistical significance. Furthermore, the Adjusted R Square value of 0.669 suggests that 66.9% of the variance in quality performance can be attributed to the combined influence of SCM, TQM, and JIT. These findings underscore the importance of implementing effective SCM, TQM, and JIT practices to enhance quality performance in manufacturing companies. By optimizing supply chain processes, fostering a culture of continuous improvement, and implementing lean production methods, companies can achieve higher product quality, customer satisfaction, and operational efficiency.